Hubungan Antara Religiusitas Dengan Perilaku Seks Bebas Pada Siswa Muhammadiyah 3 Surakarta - Salsabiela, Rizkia, Wisnu Sri Hertinjung, S.Psi, M.Psi, Psi (2017)
At this time sex is one of the problems that hit the teenager in Indonesia. This happens because of promiscuity, the influence of the media, the state of society, do not cling to religion and lack of parental supervision. Impressionable teens and debauched as not fortify the faith. Therefore, adolescents should have high religiosity to draw closer to God not to be affected in particular sexual promiscuity free. The purpose of this study was to to determine: the relationship between religiosity and sex behavior in class XI SMA Muhammadiyah 3 Surakarta, level of religiosity and the level of free sex, and how much influence (effective contribution) religiosity towards sex behavior in class XI SMA 3 Muhammadiyah Surakarta. This study uses a quantitative method. The hypothesis of this study is that there is a negative relationship between religiosity and sex behavior in class XI SMA Muhammadiyah 3 Surakarta. This study uses total sampling techniques in class XI SMA Muhammadiyah 3 Surakarta totaling 50 subjects measuring instrument used is the religiosity scale and the scale of sex behavior. Data analysis method used is the Pearson product moment correlation technique with SPSS for MS Windows version 15.00. Based on the analysis of data, the value of the correlation coefficient (r) of -0.217, p = 0.065 (p <0.05) means that there are less significant negative relationship between religiosity and free sex. The effective contribution of these two variables is shown by the determinant coefficient (r²) = 0.047 which shows that religiosity affect sex behavior amounted to 4.7% and the remaining 95.30% influenced by other variables. Free sex variables have the empirical mean (RE) of 95.78 and the mean hypothetical (RH) is 125, which means sex behavior toward religiosity is low. Variable religiosity has the empirical mean (RE) of 99.14 and the mean hypothetical (RH) of 75, which means a relatively high religiosity.